Conformal electrodes for on‐skin digitalization. (30th September 2021) - Wang, Cong; He, Ke; Li, Jiaofu; Chen, Xiaodong
Abstract: On‐skin digitalization, streamlining the concept of the "human to device to cyberspace" platform, has attracted great attention due to its vital function in remote medicine and human–cyber interfaces. Beyond traditional rigid electrodes, soft electrodes with conformal and comfortable interfaces are essential for long‐term and high‐fidelity signal acquisition. In addition, the on‐skin data processing systems will get rid of complex cables toward a vision of fascinating form, being lightweight, skin‐friendly and even imperceptible. Although numerous soft materials and devices with mechanical tolerance have been developed, the study of conformal electrodes and on‐skin digital integrated systems are still in infancy. Here, the requirements and designs of conformal electrodes, the emerging opportunities and challenges from multichannel/multifunctional sensors to a whole new on‐skin sensing platform are highlighted. Abstract : On‐skin digitalization, containing remote electrophysiological recording and analyzing, have attracted extensive attention as the vital application in modern medicine and human‐cyber interfaces. The representative achievements and forward‐looking viewpoints on conformal sensing electrodes and on‐skin digital integrated systems toward a whole new monitoring platform being lightweight, skin‐friendly and even imperceptible are highlighted.